Seed vigor of contrasting rice cultivars in response to elevated carbon dioxide - Chen, Chen; Jiang, Qian; Ziska, Lewis H.; Zhu, Jianguo; Liu, Gang; Zhang, Jishuang; Ni, Kang; Seneweera, Saman; Zhu, Chunwu (Field crops research, 2015)
Although a number of studies have shown that rising atmospheric carbon dioxide concentration, [CO2], can differentially affect the growth and yield potential of rice (Oryza sativa L.) cultivars, there has been no attempt to determine if the response is associated with changes in seed vigor, an essential aspect of crop establishment. Because previous investigations have shown that [CO2] can change the grain structure and quality of rice seed, we hypothesized that [CO2] would decrease vigor via decreased germination rates. To test this hypothesis, we used an in situ, free-air CO2 enrichment (FACE) system to assess seed quality in six rice cultivars that differed in their growth and reproductive response to rising [CO2]. Elevated [CO2] had no effect on seed hull thickness or seed specific gravity, but did significantly reduce total nitrogen and protein concentration for all cultivars. Despite the changes in grain physical and chemical traits associated with germination, no clear indication of quantitative effects of elevated [CO2] on rice germination was found.